The Effect Of Work-Life Balance On Employee Welfare Mediated By Job Satisfaction With Organizational Support As Moderation - Mariana, Gian; Arifin, Aditya; Murti, Angki Lakmi (Lentera Ilmu Nusantara, 2024)
The study aims to determine the effect of work-life balance on employee welfare mediated by job satisfaction with organizational support as moderation. The sampling method used is the purposive sampling method. The research sample used was 130 respondents. The SmartPLS (Partial Least Square) 3.0 program is used as an analysis method. The results of the study show that there is an influence of work-life balance on employee welfare. Organizational support also strengthens the influence of job satisfaction among employees of manufacturing companies in Cikarang companies.